The effect of pressure on the electronic properties of diamond crystal (Eurasian Journal of Research, Development and Innovation, 2024)
The study included the application of quantum mechanical calculations using the average neglect method of differential interference to the effect of pressure (pinch or pull stress) on the electronic properties and the extent of its effect on both the valence band width, the conduction band width, the lattice constant of the crystal, as well as the energy gap and the relationship of pressing and pulling stress with ductility, as follows :Increasing the width of both the valence and conduction bands and decreasing the energy gap in the pressing stress.